Ad Hoc and Sensor Wireless Networks: Architectures, Algorithms and Protocols - Liu, Hai; Chu, Xiaowen; Wing Leung, Yiu (Bentham Science Publishers, 2009)
This Ebook brings together the latest developments and studies of Mobile Ad Hoc Networks (MANETs) and Wireless Sensor Networks (WSNs), which should provide a seedbed for new breakthroughs. It focuses on the most representative topics in MANETs and WSNs, such as energy-efficient routing, backbone construction, multicast/broadcast, resource allocation, data gathering/aggregation, sensor coverage, target tracking, and so on. This Ebook is suitable for scholars, researchers and developers to grasp the most updated work in MANETs and WSNs. Moreover, the Ebook is a valuable companion and comprehensive reference for graduate students who are taking a course in wireless networking. Compared with existing books in the field, this Ebook focuses on general architectures, algorithms and protocols for both MANETs and WSNs, and covers heterogeneous networks where sensors are co-existing with ad hoc nodes.